Evidence for pressure induced unconventional quantum criticality in the coupled spin ladder antiferromagnet C9H18N2CuBr4 - Hong, Tao; Ying, Tao; Huang, Qing; Dissanayake, Sachith E.; Qiu, Yiming; Turnbull, Mark M.; Podlesnyak, Andrey A.; Wu, Yan; Cao, Huibo; Liu, Yaohua; Umehara, Izuru; Gouchi, Jun; et al. (Nature Communications, 2022)
There is a class of quantum phase transitions that do not fit into the traditional Landau paradigm, but are described in terms of fractionalized degrees of freedom and emergent gauge fields. Hong et al. find evidence of such a transition in a molecular spin-1/2 antiferromagnetic ladder compound under hydrostatic pressure.
CRIS-Team WoS Importer:2022-06-17